Papers from the Business Innovation in the Knowledge Economy Conference 2003 - Martin, Lynn M.; Abbott, Julie (Qualitative market research, 2004)
Consumer knowledge is a very important asset for an organisation. Two types of consumer knowledge have been identified, "knowledge about customers" including customer segments, individual customer preferences, potential customers, and "knowledge possessed by customers" including knowledge about product ranges, companies, and the marketplace. Electronic commerce (e-commerce) offers an ideal medium for the creation and exchange of both types of knowledge. This paper presents the results of an initial phase in a research cycle that looks at e-commerce through the lens of knowledge management. It